Design of novel deep-UV nonlinear optical materials with one-dimensional functional module [BO2]∞ chain and fluorine-driven short phase-matching. (November 2022) - Tudi, Abudukadi; Xie, Congwei; Pan, Shilie; Yang, Zhihua
Abstract: Design of deep-ultraviolet (deep-UV) nonlinear optical (NLO) materials is urgently needed owing to the lack of high-performance crystals to meet the contradictory criteria of deep-UV transparency, strong NLO response and moderate birefringence to reach deep-UV phase-matching. In this work, a "highly-polymerized units optimizing electron delocalization" strategy was proposed to explore novel types of deep-UV NLO anionic functional module and design new materials. Two novel NLO systems with new NLO anionic functional module-one dimensional [BO2 ]∞ chains were successfully designed. In total, four LiBO2 (I-IV) and five Li2 BO2 F (I–V) structures with good thermodynamically and dynamically stable/metastable were obtained by using evolutionary algorithm crystal structure prediction techniques. All these structures contain the [BO2 ]∞ infinite chains and have deep-UV transparency (< 177.3 nm). LiBO2 (II, IV) and Li2 BO2 F (I, IV-V) exhibit large NLO response (2.0–2.3 × KH2 PO4 ) and large birefringence (0.093–0.146 @1064 nm). Remarkably, Li2 BO2 F–I possesses an extremely short phase-matching wavelength about 159 nm, which is beneficial from the introduction of fluorine to maintain the superior functional module [BO2 ]∞ and optimize the optical properties. The results indicate that [BO2 ]∞ can be as a new deep-UV NLO functional module, this work provides an insight into the design of new deep-UV compound with outstanding NLO performances. Graphical abstract: By using a "highly-polymerized units optimizing electron delocalization" strategy and evolutionary algorithm crystal structure prediction techniques, two novel NLO systems LiBO2 and Li2 BO2 F with one-dimentional anonic framework-1D [BO2 ]∞ functional module were designed and predicted successfully. Li2 BO2 F–I has a very short phase-matching wavelength of 159 nm owing to the fluorine optimizing optical properties. Image 1 Highlights: 1D [BO2 ]∞ chain was revealed as a new deep-UV NLO anion framework. All of predicted NCS structures show excellent NLO properties. Fluorine-driven strategy was used to regulate NLO properties. A figure of merit for was proposed to evaluate the deep-UV NLO properties of the material.